A COMPARATIVE STUDY OF THE FACTORS AFFECTING THE MALE AND FEMALE STUDENTS’ ACADEMIC PERFORMANCE IN HIGHER EDUCATION (A CASE OF GOVERNMENT COLLEGE UNIVERSITY, LAHORE) - Ahmad, Muhammad Riaz; Pervaiz, Muhammad Khalid; Aleem, Muhammad (European Scientific Journal, ESJ, 2015)
The gender differences can never be ignored in any society or community in all fields of life. Similarly, Academic performance in higher education may also be influenced by gender according to the demographic behaviour and personal attitude of the students towards studies. The objective of this study is to investigate the possible differences in gender wise academic performance in higher education. A sample of 285 students was selected from Government College University, Lahore and the requisite information was collected through a questionnaire which was developed for this purpose. The reliability of the instrument/questionnaire was measured by Cronbach Alpha. Descriptive and inferential measures were used to explain the factors affecting the students‘ academic performance. Furthermore, the levene’s and t-tests are used for inferential analysis. The software SPSS (Version-16) was used for the data analysis. The Levene's test suggested that the variances of both male and female students’ performance were equal with F = 2.16 at p-value=0.143 and pooled t-test analysis has suggested that the average percentage marks of male and female students’ are significantly different with t = 2.206 having p-value= 0.028. The averages of the performance of male and female students were 72.12 and 74.54, respectively. The performance of female students’ in higher education is found to be better as compared to the male students.